218k views
2 votes
√ 25 –2√3 + √27 +2√ 9 Express in simplified radical

√ 25 –2√3 + √27 +2√ 9 Express in simplified radical-example-1
User Coto
by
6.0k points

1 Answer

2 votes

Answer:

The expression in simplified radical form is:

√ 25 –2√3 + √27 +2√ 9 = 11 + √3

Explanation:

Given the expression

√ 25 –2√3 + √27 +2√ 9

as

√ 25 = 5

√27 = 3√3

2√9 = 6

so the expression becomes

√ 25 –2√3 + √27 +2√ 9

= 5 - 2√3 + 3√3 + 6

= 11 + √3

Thus, the expression in simplified radical form is:

√ 25 –2√3 + √27 +2√ 9 = 11 + √3

User Aafreen Sheikh
by
6.1k points